Book Reviews. (1st August 2007) - ,
Abstract : BOOK REVIEWS John Wills, Conservation Fallout: Nuclear Protest at Diablo Canyon (HORACE HERRING) Frank Uekoetter, The Green and the Brown: A History of Conservation in Nazi Germany (CHRIS PEARSON) Edward I. Steinhart, Black Poachers, White Hunters: A Social History of Hunting in Colonial Kenya (TOBIAS J. LANZ) T.C. Smout, Alan R. MacDonald and Fiona Watson, A History of the Native Woodlands of Scotland, 1500-1920 (JAN OOSTHOEK) Stephen R. Mark, Preserving the Living Past: John C. MerriamÕs Legacy in the State and National Parks (PETER COATES) Harold K. Steen (ed.), Jack Ward Thomas: The Journals of a Forest Service Chief (JAN OOSTHOEK)